1999
DOI: 10.1007/s11738-999-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyamines in the cytokinin-dependent physiological processes. I. Effect of benzyladenine on polyamine levels during chloroplast differentiation in the tissue culture of Dianthus caryophyllus

Abstract: Tissue culture of Dianthus caryophyllus L. (cv. William Sire.) obligatory requiring N6-bermyladenine for greening provides a good system to study the interactions between cytokinins and polyamines. Polyamines were analyzed as dansyl derivatives which are separated by thin layer chromatography and detected by fluorescence spectrophotometry.Green callus growing on benzyladenine -containing medium showed decrease in the contents of free, conjugated and bound putrescine and spermidine in comparison to chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been shown that in green tissue culture of Dianthus caryophyllus L. (cv. William Sim), which required N 6 -benzyladenine for greening, a significant increase in the level of Put, Spd and Spm bound to plastid membranes was observed in comparison to the control (chlorophyll-less callus) (Legocka and _ Zarnowska 1999). Kotzabasis et al (1993a, b) and Del Duca et al (1994) reported that the main polyamines: Put, Spd, Spm are associated with the light-harvesting complex (LHC) and the photosystem II (PSII) of spinach and Helianthus tuberosus.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been shown that in green tissue culture of Dianthus caryophyllus L. (cv. William Sim), which required N 6 -benzyladenine for greening, a significant increase in the level of Put, Spd and Spm bound to plastid membranes was observed in comparison to the control (chlorophyll-less callus) (Legocka and _ Zarnowska 1999). Kotzabasis et al (1993a, b) and Del Duca et al (1994) reported that the main polyamines: Put, Spd, Spm are associated with the light-harvesting complex (LHC) and the photosystem II (PSII) of spinach and Helianthus tuberosus.…”
Section: Introductionmentioning
confidence: 92%
“…As suggested by Legocka and _ Zarnowska (1999 polyamines might be involved in cytokinin-mediated mechanisms of chloroplast differentiation in tissue culture of carnation, expansion of cucumber cotyledons or gametophore bud formation of moss. It has been shown that in green tissue culture of Dianthus caryophyllus L. (cv.…”
Section: Introductionmentioning
confidence: 97%
“…These effects on PA distribution within the plant could be linked to those related to CKs. In fact, some studies have reported that CK application caused significant increases in put concentration in excised cotyledons (Legocka and Zarnowska, 1999;2000;Sobieszczuk-Nowicka et al, 2007). These studies showed that this increase in put was not essential for the CK-induced expansion of cotyledons (Legocka and Zarnowska, 2000).…”
Section: Shoot Dry Weigh (G)mentioning
confidence: 99%
“…cotyledons (Cho 1983), C. sativum cotyledons (Legocka and Żarnowska 2000, Suresh et al 1978, Walker et al 1988) and C. purpureus tissue culture (Legocka and Żarnowska 2002). Furthermore, our previous study (Legocka and Żarnowska 1999) suggested that cytokinin‐induced chloroplast differentiation in carnation tissue may be partly mediated by PAs bound to thylakoid membranes, but the molecular mechanism still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%